Acute paraplegia in a patient with eosinophilic granulomatosis and polyangiitis with 20 years of evolution: case report - Guerra, Mariana; Marado , Daniela; Fortuna, Jorge (Acta Biomedica Atenei Parmensis, 2023)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare and necrotizing vasculitis of small and medium vessels with a heterogeneous presentation, multiorgan involvement, characterized by the presence of chronic rhinosinusitis, asthma, and peripheral eosinophilia. Nervous system involvement is frequent, especially in the peripheral nervous system (PNS), in the form of mononeuritis multiplex. However, subarachnoid and cerebral hemorrhage, cerebral infarction, cranial nerve palsies, and cortical blindness have also been reported in the literature. Initial therapy involves systemic GC, which are not free of complications.We present the case of a patient with EGPA of more than 20 years duration who suddenly developed bilateral paresthesia of the lower limbs and urinary retention. The neurological exam revealed paraplegia with a sensorial level in D4; the MRI showed spinal cord compression in the D2-D7 level, and the patient was emergently submitted to surgical decompression. The histopathology of the surgical specimen demonstrated the presence of epidural adipose tissue with multiple vasculitic lesions.The effects of systemic corticosteroid therapy may contribute to abnormal fat deposition in various body segments, including the neuroaxis, leading to the development of epidural lipomatosis. However, the intra-lesional vasculitic character is a unique manifestation of myelopathy that has shown us to have a more aggressive attitude.